2019
DOI: 10.1002/cncr.32069
|View full text |Cite
|
Sign up to set email alerts
|

Biopharmacological considerations for accelerating drug development of deguelin, a rotenoid with potent chemotherapeutic and chemopreventive potential

Abstract: Deguelin is a rotenoid compound that exists in abundant quantities in the bark, roots, and leaves of the Leguminosae family of plants. An analysis of evidence from both in vitro and in vivo studies suggests that deguelin displays potent anticancer activity against multiple cancer types and exhibits chemopreventive potential in Akt‐inducible transgenic mouse models. Deguelin appears to impede carcinogenesis by enhancing cell apoptosis and hindering malignant transformation and tumor cell propagation. Crucial on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 67 publications
(127 reference statements)
0
25
0
Order By: Relevance
“…Interestingly, it has been known that plants containing high deguelin have been used as an anthelmintic agent in certain regions of China [ 113 ] and as a traditional Thai medicine to treat hepatitis and hepatic dysfunction [ 114 ]. Recently, deguelin has been shown to have potent anticancer activity against multiple cancer types and can impede carcinogenesis by enhancing cell apoptosis and preventing malignant transformation and tumor proliferation [ 115 ]. Tephrosia species or chemotypes with high deguelin contents but low levels of rotenone could be ideal plant materials for developing botanical insecticides.…”
Section: Concerns Over the Use Of Tephrosia Spementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it has been known that plants containing high deguelin have been used as an anthelmintic agent in certain regions of China [ 113 ] and as a traditional Thai medicine to treat hepatitis and hepatic dysfunction [ 114 ]. Recently, deguelin has been shown to have potent anticancer activity against multiple cancer types and can impede carcinogenesis by enhancing cell apoptosis and preventing malignant transformation and tumor proliferation [ 115 ]. Tephrosia species or chemotypes with high deguelin contents but low levels of rotenone could be ideal plant materials for developing botanical insecticides.…”
Section: Concerns Over the Use Of Tephrosia Spementioning
confidence: 99%
“…Current data indicate that deguelin could be equal to or more important than rotenone in pest management. Deguelin has been widely used as pharmaceutical compounds [ 115 ], its use as an insecticide may be environmentally more benign than rotenone. Thus, the potential of deguelin deserves future investigation.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Accumulating evidence reveals that the natural product deguelin exhibits profound anti-cancer potentials in multiple human cancer models, including lung cancer 14 , hepatocellular carcinoma 15 , colorectal cancer 16 , esophageal carcinoma 17 , metastatic melanoma 18 , and breast cancer 19 . The molecular mechanism studies showed that delay of cell cycle progression by inhibition of Aurora B kinase, regulation of metabolisms, such as suppression of glycolysis, down-regulation of angiogenesis and metastasis, and activation of intrinsic apoptosis were related to deguelin-mediated anti-tumor effect [20][21][22] . However, the effect of deguelin on EGFR signaling, as well as its inhibitory efficacy on both gefitinib sensitive and resistant cells, was not clear.…”
Section: Introductionmentioning
confidence: 99%
“…f. (Leguminosae) is a plant species reported to be used widely for its medicinal, insecticidal, and soil enrichment potential in tropical Africa [1][2][3][4][5][6]. Specifically, research on T. vogelii reported medicinal properties such as anti-cancer activity [7][8][9] and efficacy as an ectoparasite treatment for domestic animals including poultry [10][11][12][13][14]. A number of studies have sought to validate the reported use of T. vogelii as a botanical insecticide under laboratory and field conditions and have reported its effectiveness for crop protection and reduced impacts on beneficial ecosystem services [15][16][17].…”
Section: Introductionmentioning
confidence: 99%